Grupo Totem: a infecção pela performance e a encenação performática - Nascimento, Frederico do (2012)
The issue of creating productions of hybrid matrices has demanded, for more than three decades, the attention of several theater theorists (COHEN: 1995; LEHMANN: 2007). The study of philosophers (DELEUZE & GUATTARI: 1995) has contributed for new concepts of the scene. These artistic practices, depending on the context, have been generating, more and more, new ways of staging. I will discuss the contamination caused by Antonin Artaud in contemporary theater, and the theater s infection by the performance, based on the thought of Barbara Browning (1995), from its capacity to penetrate and invade territories, and installs a new system. I affirm that the Totem Group (Recife PE) was contaminated by the performance and analyze two performative plays of the group, their points of convergence and separation. The first one is Ita, the search for the origin, the animal devir; the second is Caosmopolita, the body as a reflex of urbanity